The role of CRYAB in tumor prognosis and immune infiltration: A Pan-cancer analysis - Cheng, Lang; Zou, Xiong; Wang, Jiawei; Zhang, Jiange; Mo, Zengnan; Huang, Houbao (Frontiers in Surgery, 2023)
Purpose: There is evidence that the Crystallin Alpha B (CRYAB) gene is involved in the regulation of the tumor microenvironment and influences tumor prognosis in some cancers. However, the role of CRYAB gene in prognosis and immunology in pan-cancer is still unclear. Methods: In this study, we analyzed the transcriptional profiles and survival data of cancer patients from The Cancer Genome Atlas (TCGA) database. CRYAB gene and its relationships with pan-cancer were analyzed using R packages, TIMER2.0, GEPIA2, Sangerbox, UALCAN, cBioPortal, ESTIMATE algorithm, and STRING. Besides, real-time fluorescence quantitative polymerase chain reaction (RT-qPCR) was utilized to detect CRYAB expression in KIRC and a human KIRC cell line (Caki-1). Results: We found that CRYAB expression was different in tumors and adjacent tumors in human cancers, affecting patients’ prognosis in 15 cancer types. Additionally, CRYAB expression significantly correlated with tumor microenvironment (TME), immune checkpoints (ICP), tumor mutational burden (TMB), and microsatellite instability (MSI) in human cancers. Besides, CRYAB expression was positively associated with the immune infiltration of cancer-associated fibroblasts (CAFs) and endothelial cells in most human cancers. Based on enrichment analysis, the most prevalent CRYAB gene mechanism in malignant tumors may be through anti-apoptotic activity. Moreover, some FDA-approved drugs were found to be associated with CRYAB and might be potential cancer therapeutic candidates. Conclusions: CRYAB is a crucial component of the TME and influences immune cell infiltration, making it a promising biomarker to assess immune infiltration and prognosis in many malignancies.